MENGEKSPLORASI IMPLEMENTASI KEPEMIMPINAN ADAPTIF DI SEKOLAH ISLAM TERPADU - Hamdan, Hamdan; Aprina, Astia; Rochman, Maman; Husnurijal, Husnurijal; Eliana, Lia; Rahmawati, Indah (FASTABIQ: JURNAL STUDI ISLAM, 2023)
This article intends to analyze the implementation of adaptive leadership principles in SD Islam Terpadu Al Adha Kuningan. The era of disruption is a time of changes in the system of human life including education. Adaptive leadership is a leadership style that is considered relevant to be applied in an era of disruption that is difficult to predict. The application of adaptive leadership is reflected in the implementation of key principles, namely the application of context understanding, the principle of long-term thinking, the principle of commitment to continuous change, and the principle of continuous learning.   The method used is a case study. The results showed that SD Islam Terpadu Al-Adha Kuningan has implemented the principle of understanding the context reflected in the concept of establishing a school formed from the results of identifying community needs. In addition, understanding the context is also reflected in the school's process of compiling its Islamic curriculum. The principle of long-term thinking has also been implemented in SD Islam Terpadu Al-Adha Kuningan which is reflected in the development of long-term vision, action plans and improving the quality of the school team's abilities. The principle of commitment to sustainable change has also been implemented in SD Islam Terpadu Al-Adha Kuningan which is reflected in the loyalty of teachers and staff who still survive at SD Islam Terpadu Al-Adha. Furthermore, there is a school program that seeks to strengthen a sense of kinship in schools. Meanwhile, Al-Adha Kuningan Integrated Islamic Elementary School on the principle of continuous learning has not been fully implemented. This is reflected in the development of learning is still student-oriented. Keywords: Disruption; Adaptive Leadership; Principles of Adaptive Leadership